(3CTcGd GdJCSjSs - (3TeS GdOjf eMeO Hf CTQa GdSeQbfOis; (3GbdjOSs
(3ChdgG (B:s
(3hHYO aEf LeGYI ef GdaVdGA hWGFaI ef GdCUObGA EdJeShG efi QSGdI dJchf dg ebOeI hBdg ai GbJfGA dHQGgjf GdYdhe GdMSGHjI s
(3BNQgG (B:s
(3SQjY L H eJSGhjkG hGddg JYGdi SHMGfg CYde hGdMeO ddg hMOg hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3Bjg Gddg GdMcje GdYGeI (B_ (3GdfLa (B(376) s
Keywords: (3GdQjGVjGJs